2012
DOI: 10.1530/eje-11-1029
|View full text |Cite
|
Sign up to set email alerts
|

TSH-suppressive doses of levothyroxine are required to achieve preoperative native serum triiodothyronine levels in patients who have undergone total thyroidectomy

Abstract: Objective: Thyroidal production of triiodothyronine (T 3 ) is absent in patients who have undergone total thyroidectomy. Therefore, relative T 3 deficiency may occur during postoperative levothyroxine (L-T 4 ) therapy. The objective of this study was to evaluate how the individual serum T 3 level changes between preoperative native thyroid function and postoperative L-T 4 therapy. Methods: We retrospectively studied 135 consecutive patients with papillary thyroid carcinoma, who underwent total thyroidectomy. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
91
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(102 citation statements)
references
References 21 publications
10
91
1
Order By: Relevance
“…In contrast, Ito et al (33) showed that in patients who have undergone thyroidectomy, a moderately TSH-suppressive dose of L-T 4 is required to postoperatively restore serum FT 3 to the preoperative level. Interestingly, earlier studies have also indicated that L-T 4 replacement aiming at a normal serum TSH may not invariably result in an appropriate normalisation of serum FT 3 (34).…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, Ito et al (33) showed that in patients who have undergone thyroidectomy, a moderately TSH-suppressive dose of L-T 4 is required to postoperatively restore serum FT 3 to the preoperative level. Interestingly, earlier studies have also indicated that L-T 4 replacement aiming at a normal serum TSH may not invariably result in an appropriate normalisation of serum FT 3 (34).…”
Section: Discussionmentioning
confidence: 94%
“…Low total or fT3 levels have been described in many LT4-treated euthyroid subjects (reviewed by Jonklaas et al) (27), with one study showing that TSH levels below the reference range were needed to restore T3 levels to presurgery levels in patients after thyroidectomy (28). Two recent crossover studies randomized hypothyroid subjects on stable LT4 doses to continued LT4 therapy versus LT3 or desiccated thyroid extract, maintaining similar TSH levels within the reference range (29,30).…”
Section: Lt4 Therapy Energy Expenditure and Body Compositionmentioning
confidence: 99%
“…A relative T 3 deficiency may thus be present in athyreotic patients during T 4 monotherapy. Several studies (2,3,4,5) compared postoperative T 3 levels in patients on L-T 4 therapy with their own preoperative levels or those in euthyroid controls. We reported that serum T 3 levels were inappropriately low in patients who had undergone a total thyroidectomy (TT) and were on L-T 4 supplementation and that a moderately thyroid-stimulating hormone (TSH)-suppressive dose of L-T 4 was required to achieve their preoperative native serum T 3 levels (2).…”
Section: Introductionmentioning
confidence: 99%